Psychological capital, mindfulness, and teacher burnout: insights from Chinese EFL educators through structural equation modeling - Liu, Dongxia; Du, Ruikang (Frontiers in Psychology, 2024)
Objective: This cross-sectional study employs Structural Equation Modeling (SEM) to examine the relationships among psychological capital, mindfulness, and teacher burnout in a sample of 387 Chinese English as a Foreign Language (EFL) educators.Methods: Self-reported data were analyzed to investigate the direct and indirect effects of psychological capital on teacher burnout, with mindfulness serving as a potential mediator.Our SEM analysis reveals a significant direct negative association between psychological capital and teacher burnout. Moreover, mindfulness significantly mediates the relationship between psychological capital and burnout, indicating that higher psychological capital leads to increased mindfulness, which subsequently reduces burnout.This study underscores the importance of psychological capital and mindfulness in mitigating teacher burnout among Chinese EFL educators. The findings suggest that interventions targeting both psychological capital and mindfulness practices could bolster teacher well-being and foster a more positive educational environment.